Polymorphisms, differentiation, and phylogeny of 10 Tibetan goat populations inferred from mitochondrial D-loop sequences. (3rd April 2018) - Deng, Juan; Feng, Jing; Li, Li; Zhong, Tao; Wang, Linjie; Guo, Jiazhong; Ba, Gui; Song, Tianzeng; Zhang, Hongping
Abstract: China has abundant population of Tibetan goats, but available information regarding genetic structure and phylogenetic status remains limited. Here, 130 mitochondrial D-loop sequences of individuals from 10 Tibetan goat populations located in distinct plateau areas were analyzed. Eighty-six haplotypes were defined, among which 97.7% were group-specific haplotypes. Haplotype and nucleotide diversity indices were 0.990 ± 0.003 and 0.0145 ± 0.0013, respectively. The pairwise Wright's F -statistics ranged from −0.028 to 0.385, and over half of them were greater than 0.05, indicating apparent genetic differentiation among the populations. AMOVA analysis ( FST = 0.0858) manifested that the genetic structure has become weak. Phylogenetic trees revealed four haplogroups (A, B, C, and D), suggesting that Tibetan goats had four origins. Mismatch distribution analyses and neutrality tests indicated that at least one population expansion event occurred during the demographic history of Tibetan goat. These results will provide a more complete understanding of Tibetan goat genetic resources.